2015
DOI: 10.1182/blood.v126.23.4867.4867
|View full text |Cite
|
Sign up to set email alerts
|

Philadelphia Positive Acute Lymphoblastic Leukemia (Ph+ ALL), Tawam Experience

Abstract: Acute lymphoblastic leukemia (ALL) is a relatively rare lymphoid disorder with approximately 11 cases per million persons per year in United States. It is seen more commonly in children however adults are also affected with the median age approximately 39 years. The prognosis is influenced by the age of the patient and genetic findings. Abnormal cytogenetic is present in approximately 80 % of the patients. Philadelphia chromosome t (9;22) is seen in approximately 30 % of adult patients (Ph + ALL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Alam et al reported real-world data from six patients in Tawam Hospital, UAE, who were on TKI therapy for 11 years and had undetectable levels of BCR-ABL1 transcript for more than 2 years. Following a trial of TFR, half of the patients reached the six-month milestone: two remained at undetectable levels, one patient had MR4.49, and none of the patients experienced TKI withdrawal syndrome [17]. Another study at the Kuwait Cancer Control Center analyzed data from 42 patients who had a trial of TFR.…”
Section: Discussion and Expert Opinionmentioning
confidence: 99%
“…Alam et al reported real-world data from six patients in Tawam Hospital, UAE, who were on TKI therapy for 11 years and had undetectable levels of BCR-ABL1 transcript for more than 2 years. Following a trial of TFR, half of the patients reached the six-month milestone: two remained at undetectable levels, one patient had MR4.49, and none of the patients experienced TKI withdrawal syndrome [17]. Another study at the Kuwait Cancer Control Center analyzed data from 42 patients who had a trial of TFR.…”
Section: Discussion and Expert Opinionmentioning
confidence: 99%
“…Optymalnym leczeniem była polichemioterapia jak w innych ALL; po uzyskaniu całkowitej remisji (CR) u chorych w dobrym stanie z dobranym dawcą szpiku zalecano przeszczepienie allogenicznych krwiotwórczych komórek macierzystych (allo-HSCT, allogeneic hematopoietic stem cell transplantation), co istotnie poprawiło wyniki leczenia [1,2]. Istotną poprawę rokowania w tej grupie chorych przyniosło zastosowanie TKI w połączeniu z chemioterapią [3][4][5]. Początkowo stosowano jedynie imatynib, w ostatnich latach wykazano jednak, że TKI drugiej i trzeciej generacji powodują szybszą i głębszą remisję białaczki [6][7][8][9][10].…”
Section: Wprowadzenieunclassified
“…In 80% of patients with ALL, genetic aberrations can be found in the leukemic cells [ 2 , 3 ], the most common lesion being the Philadelphia chromosome with its translocation t(9;22) accountable consecutively for the most common genetically defined subtype of adult ALL. Between 20 to 30% of all adult ALL patients and more than 50% of patients in the age group above 60 years carry this lesion associated with a dismal prognosis [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%